1980
DOI: 10.2170/jjphysiol.30.955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical training on the calf and thigh blood flows.

Abstract: Summary Blood flows of the calf and thigh at rest and after submaximal and maximal exercise were determined by the venous occlusion method in 6 healthy subjects before and after physical training for 5 weeks.It was found that the magnitude of the flow after training was significantly (p<0.05)decreased when measured immediately after submaximal exercise,while there were no significant differences found with respect to both calf and thigh blood flows measured immediately after maximal exercise before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Our findings stand in contrast to other studies of different training duration or muscle groups [1,11,15]. For example, Yasuda et al reported an increase in FBF in the ipsi-and contralateral arm following 6 weeks of HG exercise training [15] and attributed the improvements to changes in neurogenic balance [15].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings stand in contrast to other studies of different training duration or muscle groups [1,11,15]. For example, Yasuda et al reported an increase in FBF in the ipsi-and contralateral arm following 6 weeks of HG exercise training [15] and attributed the improvements to changes in neurogenic balance [15].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, other investigators report a reduction in limb blood flow following short-term training programs. Bond et al [1] attributed reductions in leg blood flow to an increase in muscle cross-sectional area without proportional changes in microvascular density, whereas Saito et al attributed the lower leg blood flow to a more effective metabolic process [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although NIRS technique measured the muscle O 2 balance between supply and utilization, muscle deoxygenation after training in MI may be partly explained by the increase in muscle O 2 consumption of exercising muscle. Another possibility for enhanced muscle deoxygenation during submaximal exercise is reduced muscle blood flow caused by exercise training, as seen in previous studies of healthy subjects (Saito et al 1980 ) and post-MI patients (Clausen and Trap-Jensen 1970 ). However, VO 2 during submaximal exercise was significantly higher after training in this study (as described below).…”
Section: Discussionmentioning
confidence: 82%
“…The lower blood flow during submaximal exercise or depressed post-exercise hyperemia was observed in the calf of trained subjects in comparison with untrained ones (ELSNER and CARLSON,1962;VARNAUSKAS et al, 1970;PHILIPPI et a!.,1973 ;SAITO et a!.,1980). These results suggest that training brings about a more effective utilization of the available leg blood flow for metabolic processes even at a lower flow.…”
Section: Discussionmentioning
confidence: 92%